Effects of pushing techniques during the second stage of labor: A randomized controlled trial - DEMİRCİ, NURDAN (ELSEVIER TAIWAN, 2017)
Objective: Spontaneous pushing is a method that is used in the management of the second stage of labor and suggested to be more physiological for the mother and infant. The present study aims to evaluate the effects of pushing techniques on the mother and newborn. Materials and methods: This randomized prospective study was performed between June 2013 March 2014 in a tertiary maternity clinic in Istanbul. 80 low risk, nulliparous cases were randomized to pushing groups. Valsalva pushing group was told to hold their breath while pushing. No visual-verbal instructions were given to spontaneous pushing group and they were encouraged to push without preventing respiration. Demographic data, second stage period, perineal laceration rates, fetal heart rate patterns, presence of meconium stained amniotic liquid, newborn APGAR scores, POP-Q examination and Q-tip test results were evaluated in these cases. Results: The second stage of labor was significantly longer with spontaneous pushing. Decrease in Hb levels in valsalva pushing group was determined to be higher than spontaneous pushing group. An increased urethral mobility was observed in valsalva pushing group. Conclusions: Although the duration of the second stage of labor was longer compared to valsalva pushing technique, women were able to give birth without requiring any verbal or visual instruction, without exceeding the limit value of two hours and without affecting fetal wellness and neonatal results. (C) 2017 Taiwan Association of Obstetrics & Gynecology. Publishing services by Elsevier B.V.
Keywords: Second stage of labor; Spontaneous pushing; Valsalva; Pushing methods; Pelvic organ prolapse; EPIDURAL ANALGESIA; 2ND STAGE; BIRTH; OXYGENATION; OUTCOMES; TRAUMA; WOMEN